The palladinium catalyzed activation of bifunctional vinyl halide a-Bromoacrylic amides with 1, 3 dines and Alkynes (International Journal of Engineering and Computer Science, 2013)
A development of prospective synthetic methods to produce Pyridine including those of complex structure will allow to makes the latter more available and hence Pyridine bases will be widely used in industry. In this paper the Hetrocyclization of Acetylenes with nitriles catalyzed by palladinium Complex has been carried out. We have limited our aim to study the palladinium catalyzed activation of bifunctional vinyl halide a-Bromoacrylic amides with 1, 3 dines and alkynes to form an unsaturated butyrolactums. The compounds so obtained is 1.1-(4- Methoxyphenyl)-3(1 phenyl-(E)- methylidene)- 2,3,3a,4,5,7a- hex hydro- 1H-2-indolone and 1N-(4-Methoxyphenyl)-2-bromo-3-phenyl-(Z)- 2-propenamide